Bio-based Plastic: From Being Recyclable to Being Biodegradable - Pabico , Jonnel K. (Research Aspects in Chemical and Materials Sciences Vol. 6, 2023)
Plastics is already an integral part of man’s daily lives. Whatever man is doing, wherever man is moving, he will use plastic. Decades of experiences from plastic manufacturers led to the versality, flexibility and applicability in almost every activity man could ever had. But the affordability and availability of plastics lead human to a throw-away culture, that results to severe plastic pollution both in grounds or in waters. In the Philippines alone, 163 million plastic sachet packets, 48 million shopping bags, and 45 million thin film bags are used daily, with approximately 0.28 - 0.75 million tons dropped into the ocean each year. Plastics cannot be totally replaced with other materials. There are products, containers, bottles that can be used as replacement but the superior qualities of plastics make it the first choice of everyone. In well populated cities and countries with lesser natural resources, replacing plastics with organic materials like papers poses worse environmental footprints. As it is seen that plastics are irreplaceable, and to mitigate the problems on plastics, lots of international projects and collaborations that aims to developed technologies and system that will replace fossil-based plastics with biodegradable, recyclable, bio-based plastics and create the circular economy of plastics, aside from the plastic waste management projects such as the 3R’s, the ecoloop, etc. Prevention is better than cure. While every country implements waste management, there are pilot projects that manufactures bio-based or biodegradable plastics. The main objective is to use biodegradable materials in manufacturing plastic materials making the product biodegradable plastics. The Project ‘PEFerence’ and the ‘Project Effective are two huge international and inter-industry collaborations funded by the European Union to pilot manufacturing bio-based plastics. With the production and process being perfected through times, it is expected that the capability of the projects to manufacture more bio-based plastics and the utilization of such products will eventually increase, and decrease the price.